Umami and saltiness enhancements of vegetable soup by enzyme-produced glutamic acid and branched-chain amino acids - Sakai, Kiyota; Okada, Masamichi; Yamaguchi, Shotaro (Frontiers in Nutrition, 2024)
Introduction One major challenge of reducing salt content in food is the risk of the overall taste becoming bland. Enhancing saltiness is an effective strategy for salt reduction, and the development of salt-reduced foods using these saltiness-enhancing flavorants as food additives is underway. However, an increasing number of consumers demand a reduction in additives in clean-label foods. Objective Enzyme processing of food is an attractive strategy for developing clean-label foods because enzymes are not considered additives. We aimed to improve the saltiness and umami intensity of vegetable soups by enzyme treatment while meeting clean-label requirements. We first optimized the enzymatic reaction conditions of a protease and glutaminase blend and then investigated the synergistic effects of this enzyme blend on the taste of vegetable soup. Results Sensory evaluations indicated that the reaction products (e.g., protein hydrolysates or amino acids) could enhance the umami, kokumi, and saltiness intensity of vegetable soup supplemented with 0.5% NaCl. Notably, the saltiness intensity ratio of the enzyme-treated soup with 0.50, 0.45, and 0.40% NaCl were increased by 1.31-, 1.16-, and 0.99-fold, respectively, when this ratio for the control soup with 0.50% NaCl was set to 1.0. This indicates a 20% salt reduction rate can be achieved by enzyme treatment. Moreover, we found that these enhancements were synergically caused by enzyme-produced glutamic acid and branched-chain amino acids. Conclusion Our findings suggest that using enzyme blends of bacterial and fungal proteases and glutaminase is an effective approach to enhancing the saltiness levels of vegetable soups while meeting clean-label requirements.